Understanding Global Street Food Consumer Behavior and Experience: A Narrative Review of Literature and Development of Framework - Samit Chakravorti (Journal of Applied Marketing Theory)
This paper explores global street food consumer behavior and consumption experience. The aim of this paper is to gain a holistic comprehension of street food consumption decision making and experience through exploring nature and sources of perceptions, attitude and expectations surrounding street food, the characteristics of the product offering and the domain within which it is served and consumed. To achieve this aim the author engages in a narrative review of academic research on consumer behavior of street food, provides a holistic picture of consumption experience of street food through consolidating and interpreting research findings, and extends the theoretical understanding of street food consumption experience through development of a global consumer decision making framework. The review indicates that there is a growing interest in street food consumer behavior research. Studies have been done across many countries and published across a diverse set of multidisciplinary journals. Research findings from the selected articles collectively indicate that street food experience is multifaceted, includes cognitive and affective components, and happens at the meeting point of consumer psychology surrounding street food and the multi touch point dimensions of the experiencescape of street food. Tourists and domestic consumers seem to be cautiously enthusiastic about consuming street food, seeing benefits in an affordable, convenient, cultural, authentic, traditional and out of the routine experience but also risks about food safety. Consumers think vendors provide ample smell, taste, texture, appearance, flavor and fresh food at a value price and proficient service which is a big draw. At the same time, they have shown concerns about safe handling of food and desire several improvements in the areas of interaction, engagement and an enjoyable physical environment. Practical implications for street food businesses and street food destination tourism administrators are discussed and future research areas for academia recommended.